Иван: повесть : [для среднего и старшего школьного возраста] / В. Богомолов ; рисунки В. Любарца - Богомолов Владимир Осипович (Удмуртия, 1984)
Экземпляры: КР (20020330) / Инвентарный номер: у33707 / Сис.шифр: Р2 / Авт.знак: Б 74 / ГРНТИ: 17.82 / ББК: 84(2)